Acetazolamide-induced bilateral uveal effusion after cataract surgery - Abhinay Ashok; Manoj Y Bhat; Rashmi Shetty (TNOA Journal of Ophthalmic Science and Research, 2023)
Idiosyncratic reactions to a large number of drugs have been reported to cause choroidal detachment and secondary angle-closure glaucoma (ACG). We report a case of bilateral acute ACG and peculiar choroidal effusion following the administration of oral acetazolamide immediately after cataract surgery. Few cases of acute secondary ACG with choroidal effusion and anterior shift of the lens-iris diaphragm have been associated with acetazolamide compared with other sulfonamides. As far as we are aware, posterior involvement with retinal folds and papillary edema due to acetazolamide has not been described before.